Vinland saga. Book ten - Yukimura, Makoto, 1976- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2018)
After months of hard labor as a farm slave, Thorfinn begins to realize what his father meant by the words, “A true warrior needs no sword.” Perhaps he can find a new purchase on life in the mysterious land he heard tell of in his childhood: the continent to the west known as Vinland.